AN ERROR ANALYSIS OF TRANSLATION FROM TETUM TO ENGLISH AT FIRST GRADE SECONDARY SCHOOL COLÉGIO PAULO VI DILI - TIMOR LESTE IN ACADEMIC YEAR 2017 - NURHAYATI, AGUSTINA (IJRDO- Journal of Educational Research, 2017)
Timor Leste is one of the countries in the world that uses the two Official Languages(Officially Bilingual), namely Portuguese and Tetum. Both the languages and used as a communicationtool in the office, school or other places. While English used as working language and compulsorysubject in school and university. In the schools, English is taught as second language. Students oftenhave difficulty in understanding English texts. To facilitate better understanding of vocabulary andgrammar, they are likely to translate into Tetum language or vice versa. However, in translation oftenencounter several errors.This study aims to determine what are problems faced by students when they translate text fromEnglish language to Tetum language. In addition to analyze kinds of errors that they write in text whichthey translate and analyze source of error. Method used for this research is descriptive qualitativemethod, while the samples used in twelve classes only taken one class to research using randomsampling. To obtain data in this study, the writer uses text in Tetum with the title "Wainhira ita lokonetika" or "When did we lose ethics?" Which will be translated into English, the author also conductedobservation studies that aims at determining problems arise in classroom when students are beingtranslated the texts and interviews to some of the students to determine what problems they face whenthey translate text from Tetum to English. From the results of the study it is found that kinds of errors intranslation are: competence error, error performance, fundamentally error consisting of local and globalerror and the author uses surface strategy taxonomy such as: omission, addition, misinformation andmisordering. While the source of errors in the translation found four things, namely overgeneralization,ignorance of Rule Restrictions, incomplete application of rules restrictions and false concepthypothesized. Students have a lot of trouble for did translation. It can be seen from result of theirtranslation. In general, the students felt overwhelm and difficult to put their ideas in a coherent way.Students did not know how to write correct English sentences. They translated word by word as theresult translation has shifted from real meaning. Other problems, Students have problem in placementand the use verbs in their sentencesFrom these results the writer concluded that there is a need for a teacher to gives translation exercisesto students so that teachers can know weaknesses and shortcomings of the students through text theytranslated, for the necessity of the need for teachers to provide training on this to students, because bydoing translation can add students vocabulary, train them to construct grammatical sentences correctlybased on what they have learned in school.